Additive manufacturing toward 2D and 3D freeform lattices with conforming compliant bi-/multi-stable tiles - Gershon Elber (Graphical Models)
Compliant mechanisms have captured the attention of many researchers in recent years, with ever-expanding mechanical and physical behaviors. Moreover, the fabrication of such mechanisms has been greatly simplified with the enabling technology of 3D printing.Drawing from existing lattice construction abilities, in this work we explore the abilities of constructing whole freeform lattices, where the tiles in these lattices are compliant mechanisms, possibly heterogeneous. Specifically, herein we focus on bi-stable and multi-stable tiles, or tiles with two or more mechanical stable states. The introduced approach will be exemplified on a variety of 2D and 3D lattices, fabricated with the aid of additive manufacturing.